2017
DOI: 10.3390/f8030063
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Forest Color Characteristics and Scenic Beauty: Case Study Analyzing Pictures of Mountainous Forests at Sloped Positions in Jiuzhai Valley, China

Abstract: Abstract:Forests are important place for outdoor recreation and scenery appreciation. So in order to better meet the needs of the public, forest appreciation has received increasing attention from foresters in recent years. However, related research is still limited. Therefore, this paper seeks to examine the relationship between forest colors (measured by specific elements and spatial indices of color) and Scenic Beauty Estimation values. We researched Jiuzhai Valley in China by selecting 104 pictures to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 15 publications
3
54
0
Order By: Relevance
“…However, previous studies have found that the quality of community landscapes in a group was higher than uniformly and randomly distributed landscapes [46]. However, when investigating the degree of aggregation of landscape color patches, it was found that excessively gathered color patches may negatively affect the emotional state of people, but landscapes with more color patches are more likely to be favored by observers [32,47]. On the other hand, a colorful, attractive street edge may distract drivers, which could lead to more accidents than the "monotonous" green landscapes.…”
Section: Spatial Distribution Of Colorsmentioning
confidence: 96%
See 2 more Smart Citations
“…However, previous studies have found that the quality of community landscapes in a group was higher than uniformly and randomly distributed landscapes [46]. However, when investigating the degree of aggregation of landscape color patches, it was found that excessively gathered color patches may negatively affect the emotional state of people, but landscapes with more color patches are more likely to be favored by observers [32,47]. On the other hand, a colorful, attractive street edge may distract drivers, which could lead to more accidents than the "monotonous" green landscapes.…”
Section: Spatial Distribution Of Colorsmentioning
confidence: 96%
“…The confidentiality of each participant was assured with no data collected to associate a person to their response and respondents were not required to participate. An initial six questions (1-6) ascertained gender, age, education level, occupation, province (China province currently residing in), and work with forests (ascertained if respondent works with forests as a function of their occupation) following the methods of Zhang [32]. Respondents were then asked in following 81 questions to rate the scenic beauty of each image through the statement "Please choose the degree of beauty according to your perception" by using a seven-point evaluation method ranging from -3 (Dislike Very Much) to +3 (Like Very Much).…”
Section: Questionnaire Design Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…This vigorously promotes the development of forest-based tourism destinations and triggers visitors' pursuit of high-quality forest landscape accordingly. However, only a limited number of studies to date in China have focused on the assessment of FLQ [12,[16][17][18][19][20][21]. Theoretically or empirically, the exiting studies lag far behind the development practice of China's forest tourism [22].…”
Section: Introductionmentioning
confidence: 99%
“…As to the field of landscape architecture, plant color, as one of the most prominent aesthetic features of vegetation landscape, is always taken into account in urban greening and plant landscape design . Finer‐scaled visual assessments of color can allow us to exactly annotate plant colors, the dominant color composition in the nature world, which can shed light on a reasonable color choice in an artificial landscape design when in pursuit of a harmony with the local nature.…”
Section: Discussionmentioning
confidence: 80%